2015
DOI: 10.1149/2.0541507jes
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Reaction Kinetics in Sr-Doped La2NiO4+δRuddlesden-Popper Phase as Cathode for Solid Oxide Fuel Cells

Abstract: In this paper, electro-catalytic reduction of oxygen in Sr-doped lanthanum nickelates, La 2-x Sr x NiO 4+δ (0 ≤ x ≤ 0.4) RuddlesdenPopper (R-P) phase, has been investigated. The oxygen reduction reaction (ORR) kinetics is evaluated via electrochemical impedance spectroscopy (EIS) with the symmetric cell configuration. The maximum performance is achieved with the un-doped La 2 NiO 4+δ , ∼0.13 cm 2 at 800 • C. Sr doping decreases the electrode performance progressively. Further detailed analysis indicates that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 54 publications
(80 reference statements)
7
37
0
Order By: Relevance
“…Figure 3 shows the ECR for Sr20 and Sr40 obtained with 0.20 atm P O2 at 700 o C. Sr doping impairs the surface exchange kinetics substantially. k for Sr20 and Sr40 is 3.1×10 -6 and 1.8×10 -6 cm/s, which is in good agreement with the degradation in the electrochemical performance of lanthanum nickelate cathodes as Sr doping we reported previously (17). In order to study the possible rate-limiting step(s) in the surface oxygen exchange process and Sr effect on those steps, the reaction orders is derived and discussed.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Figure 3 shows the ECR for Sr20 and Sr40 obtained with 0.20 atm P O2 at 700 o C. Sr doping impairs the surface exchange kinetics substantially. k for Sr20 and Sr40 is 3.1×10 -6 and 1.8×10 -6 cm/s, which is in good agreement with the degradation in the electrochemical performance of lanthanum nickelate cathodes as Sr doping we reported previously (17). In order to study the possible rate-limiting step(s) in the surface oxygen exchange process and Sr effect on those steps, the reaction orders is derived and discussed.…”
Section: Resultssupporting
confidence: 86%
“…La 2-x Sr x NiO 4+δ (x=0, 0.2, 0.4) with R-P phase are first synthesized as reported elsewhere in detail (17). In short, stoichiometric nitrates together with citric acid were dissolved into distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, Guan et al . reported that the electrochemical performance of (La 1− x Sr x ) 2 NiO 4+ δ ( x =0–0.2) electrodes applied on yttria‐stabilized zirconia solid electrolyte with a CGO10 buffer layer decreases progressively with increasing Sr content ( R η =0.41 Ω cm 2 for x =0 and 14.4 Ω cm 2 for x =0.2 at 700 °C) and attributed this to a decrease of both the bulk oxygen diffusion and surface exchange rates caused by Sr substitution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the exploration of novel IT cathode materials with reduced polarization resistance is imperative to minimize the overall energy loss. In recent, A 2 BO 4+δ R-P phase lanthanum nickelates have attracted increasing research interests [7][8][9]. Such materials feature a layered structure of alternative stacking LaO rock salt with ABO 3 perovskite.…”
Section: Introductionmentioning
confidence: 99%